'Looking back, i wouldn't join up again': the lived experiences of police officers as victims of bias and prejudice perpetrated by fellow staff within an english police force. (2nd January 2020) - Zempi, Irene
ABSTRACT: Women, ethnic minority and LGB police officers often experience prejudice, disadvantage and exclusion within police forces because of their perceived 'otherness' in a predominantly white, heterosexual, male organisation. In the context of an increasingly diverse service, the paper argues that the concept of intersectionality is important in order to understand the experiences of police officers who encounter bias and prejudice because of their multiple, intersecting identities. Drawing on data from qualitative interviews with 20 individuals based in an English police force, the paper examines their occupational experiences of bias, discrimination and exclusion perpetrated by their colleagues and supervisors. Utilising the 'exit, voice and loyalty' model, the paper analyses how police officers are affected by, and respond to these experiences. Taken together, these arguments lay the foundation for future work to further understand the experiences of police officers as victims of bias and prejudice due to their multiple, intersecting identities.